Associations between education, gender, social class personality traits, and religious faith and service attendance in a British cohort. (November 2015) - Furnham, Adrian; Cheng, Helen
Abstract: This study explored the associations between social and psychological factors and religious background and service attendance in a large (N = 5955), nationally representative sample followed over 50 years in the UK. Results from regression analysis showed that sex and the Big-Five personality traits were all significantly and independently associated with religious background in adulthood. Traits Agreeableness, Extraversion, and Conscientiousness were significantly and positively associated with religious background and service attendance, whereas education and occupation, and traits Emotional Stability and Openness were negatively associated with the outcome variables. Personality was a stronger predictor of background than event attendance. Limitations of the study are acknowledged. Highlights: This study explored the associations between personality and religious background and service attendance. Sex and the Big-Five personality traits were all significantly associated with religious background in adulthood. Agreeableness, Extraversion, and Conscientiousness were positively associated with both outcome measures. Education, occupation, Emotional Stability and Openness were negatively associated with the outcome variables. Personality was a stronger predictor of background than event attendance.